2022
DOI: 10.7758/rsf.2022.8.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Native Americans and Monetary Sanctions

Abstract: This article is published under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License.ishments. Unfortunately, much of this expanding literature has focused on the experiences and impacts of systems of monetary sanctions on people who are Black, Latinx, or White- Native Americans and Monetary SanctionsroBert stewa rt, Br ie a n na wat ters, v eronica Horow it z, rya n P. l a rson, Br i a n sa rgen t, a nd cHr istoPHer uggen Native Americans are disproportionately affected by the criminal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…We also study seriously the racial contours of monetary sanctions. Several articles in this volume show that Black, Latinx, and Native Americans are disproportionately processed within the criminal legal system and, as a result, carry a disproportionate burden of criminal legal debt (Sanchez et al 2022;Bing et al 2022;Stewart et al 2022;O'Neill et al 2022).…”
Section: Contribu Tions Of T His Volumementioning
confidence: 99%
“…We also study seriously the racial contours of monetary sanctions. Several articles in this volume show that Black, Latinx, and Native Americans are disproportionately processed within the criminal legal system and, as a result, carry a disproportionate burden of criminal legal debt (Sanchez et al 2022;Bing et al 2022;Stewart et al 2022;O'Neill et al 2022).…”
Section: Contribu Tions Of T His Volumementioning
confidence: 99%
“…In contrast, only 17.2% of Hispanic AIAN people and 25.7% of multiracial non-Hispanic AIAN people lived on or near a homeland area, and the lifetime risks of imprisonment for these groups were 24.0 and 56.4%, respectively. Our data are inadequate to analyze residential variation in AIAN imprisonment risk directly, and so more research is needed to understand the role of jurisdiction in explaining AIAN people's intense but diverse exposure to imprisonment and types of criminal legal system contact (28). States, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the design and implementation of monetary sanctions across states and within them help reveal how the negative impact of monetary sanctions, and thus disproportionate punishment, is concentrated among people with low incomes and, by extension, people of color ( Bing, Pettit, and Slavinski 2022 , this volume) and people receiving public assistance ( Sykes et al 2022 , this volume). Recent work further illustrates how the negative impacts of legal financial obligations are concentrated among immigrants ( Sanchez et al 2022 , this volume) and Native Americans ( Stewart et al 2022 , this volume).…”
Section: How Monetary Sanctions Thwart Just Outcomesmentioning
confidence: 98%
“…Monetary sanctions allow people with financial means to resolve debts, fulfill sentences, and thereby absolve themselves of criminal wrongdoing. At the same time, unpaid monetary sanctions contribute to extended system involvement and legal entanglements ( Martin, Spencer-Suarez, and Kirk 2022 , this volume) that uniquely disadvantage certain subgroups of the population on the basis of ability to pay ( Bing, Pettit, and Slavinski 2022 , this volume; Sanchez et al 2022 , this volume; Stewart et al 2022 , this volume; Sykes et al 2022 , this volume; Harris 2016 ; DOJ 2015 ). The Ferguson Commission report concluded that legal financial obligations were exploitative and “disproportionately harmed defendants with low incomes” ( Ferguson Commission 2015 , 93).…”
mentioning
confidence: 99%